2001
DOI: 10.1074/jbc.m010809200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That the Peptidylprolyl Isomerase Domain of the hsp90-binding Immunophilin FKBP52 Is Involved in Both Dynein Interaction and Glucocorticoid Receptor Movement to the Nucleus

Abstract: Here, we also show that native GR⅐hsp90 heterocomplexes immunoadsorbed from L cell cytosol contain dynein and that GR⅐hsp90 heterocomplexes assembled in reticulocyte lysate contain cytoplasmic dynein in a manner that is competed by the PPIase domain of FKBP52.Steroid receptors move continuously into and out of the nucleus (Refs. 1-4; for review, see Ref. 5), and, depending upon the receptor, the hormone-free, untransformed receptor may have a predominantly nuclear or cytoplasmic localization. The hormone-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
239
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(250 citation statements)
references
References 38 publications
10
239
1
Order By: Relevance
“…Pratt and colleagues have demonstrated that components of the apoGR complex bind cytoskeletal factors (Galigniana et al, 2001). Alternatively, Kino et al (2003) have suggested that binding to the 14-3-3 protein helps tether apoGR to the cytoplasmic compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Pratt and colleagues have demonstrated that components of the apoGR complex bind cytoskeletal factors (Galigniana et al, 2001). Alternatively, Kino et al (2003) have suggested that binding to the 14-3-3 protein helps tether apoGR to the cytoplasmic compartment.…”
Section: Discussionmentioning
confidence: 99%
“…The pGEX1 T plasmid encoding the GST-rabbit FKBP52 Gly 32 -Lys 138 expression vector that comprises the PPIase core domain I (provided by Drs. Michel Renoir and Christine Radanyi, UMR8612 CNRS, Paris, France) and the purification of the PPIase core domain I protein were described previously (23,34). The mammalian expression plasmid pSG5PL-PPIase core domain I was described in a previous work (23).…”
Section: Methodsmentioning
confidence: 99%
“…GR⅐hsp90 heterocomplexes immunoadsorbed from cell lysates contain cytoplasmic dynein (23,24), a molecular motor that processes along microtubular tracks toward the nucleus (25). These heterocomplexes also contain one of several immunophilins with tetratricopeptide repeat (TPR) domains that interact with a TPR acceptor site on hsp90 (13).…”
mentioning
confidence: 99%
“…hsp90 was proposed to be a mediator of protein trafficking over a decade ago (Pratt, 1992(Pratt, , 1993. Since then, ample evidence has accumulated indicating that hsp90 is required for the subcellular targeting of a variety of proteins, including the glucocorticoid receptor (Owens-Grillo et al, 1996;Czar et al, 1997;Silverstein et al, 1999;Galigniana et al, 2001), the dioxin receptor (Kazlauskas et al, 2001), the receptor tyrosine kinase ErbB2 (Xu et al, 2002), the epidermal growth factor receptor (Supino-Rosin et al, 2000), the CFTR (cystic fibrosis transmembrane regulator) chloride channel (Loo et al, 1998) and the G-protein G␣ 12 (Waheed and Jones, 2002). hsp90 is also required for protein translocation into mitochondria (Young et al, 2003) and peroxisomes (Crookes and Olsen, 1998).…”
Section: Introductionmentioning
confidence: 99%